Fast versus gradual adaptation of soft monthly contact lenses in neophyte wearers. Issue 4 (August 2022) - Wolffsohn, James S.; Ghorbani-Mojarrad, Neema; Vianya-Estopa, Marta; Nagra, Manbir; Huntjens, Byki; Terry, Louise; Sweeney, Laura Elaine; Dutta, Debarun; Joshi, Mahesh Raj; Wright, Daniel; Bruce, Heather; Hallam, Emily; et al.
Abstract: Aim: To determine if a gradual adaptation period is necessary for neophytes when fitted with modern hydrogel or silicone hydrogel reusable disposable contact lenses. Method: Across four sites, 74 neophytes (18–28 years) were randomly assigned to a reusable lens cleaned nightly with Opti-Free® Puremoist® multi-purpose contact lens solution: Proclear® (hydrogel) or Biofinity® (silicone hydrogel) and an adaptation schedule: fast (10 h wear from the first day) or gradual (4 h on the first day, increasing their wear time by 2 h on each subsequent day until they had reached 10 h). Masked investigators graded ocular surface physiology and non-invasive tear breakup time (NIBUT) and a range of comfort, vision and lens handling subjective ratings (0–100 visual analogue scales) were recorded at the baseline visit and after 10 h of lens wear, 4–6 days and 12–14 days after lens fitting. Subjective scores were also repeated after 7 days. Results: There was no difference (p > 0.05) in ocular surface physiology or NIBUT between fast and gradual adaptation groups at any time point in either lens type with the exception of increased corneal staining (p = 0.019) in the silicone hydrogel fast adaptation group after 4–6 days, but was similar by 12–14 days. Subjective scores were also similar across the visits and lens types with the exception of 'lens awareness' (p = 0.019) which was less in the gradual versus the fast adaptation silicone hydrogel lens group at 12–14 days. Conclusion: There seems to be no clinical benefit for recommending a gradual adaptation period in new wearers fitted with modern soft reusable disposable contact lenses. The findings of this work add to a growing body of evidence suggesting that such advice is unnecessary in regular soft contact lens wear, which has important ramifications for the initial clinical management of these patients.